RHINOLOGY - Anca-Ionela Cîrstea; Maria Dana Gheorghiev; Miruna Bratiloveanu; Lorena Păun; Rareş Oancă; Remus Chirciu; Mihai Dumitru; Daniela Vrînceanu (ORL.ro)
The evolution of maxillary sinus surgery: open approaches in the era of nasal endoscopy